Riwayat Pemberian MP-ASI dan Sosial Ekonomi dengan Kejadian Stunting pada Balita - Hidayah, Astriya; Siswanto, Yuliaji; Pertiwi, Kartika Dian (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2021)
Stunting is a condition of failure to thrive in children under five due to a chronic lack of nutritional intake. According to WHO, Indonesia is the third country with the highest incidence in Southeast Asia at 27.7%. This study aims to determine the relationship between the history of complementary feeding and economic status with the incidence of stunting in children under five in Ngjajaran Village, Tuntang District, Semarang Regency. The research design used was observational analytic with a case-control approach. The research sample was 88 toddlers consisting of 22 cases and 66 controls taken by simple random sampling technique. Data were analyzed using chi-square test. The results showed that there was a relationship between the history of complementary feeding and the incidence of stunting in toddlers with p value = 0.004; OR=4.929 (95% CI 1.745-13.936); there is a relationship between economic status and the incidence of stunting in children under five with p value = 0.047; OR=0.327 (95% CI 0.120-0.890). Closing: The conclusion in this study is that there is a relationship between the history of giving complementary feeding and economic status with the incidence of stunting in children under five in Ngajaran Village, Tuntang District, Semarang Regency.